2012
DOI: 10.1111/j.1469-8137.2012.04301.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary stasis of sporopollenin biochemistry revealed by unaltered Pennsylvanian spores

Abstract: SummaryThe biopolymer sporopollenin present in the spore/pollen walls of all land plants is regarded as one of the most recalcitrant biomacromolecules (biopolymers), providing protection against a range of abiotic stresses. This long-term stability is demonstrated by the near-ubiquitous presence of pollen and spores in the fossil record with spores providing the first evidence for the colonization of the land.Here, we report for the first time chemical analyses of geologically unaltered sporopollenin from Penn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
63
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 26 publications
3
63
0
Order By: Relevance
“…Similar INA efficiencies for capsule and heated vial spores indicate that heating did not adversely impact any spore coat characteristics that might be responsible for the spore's ability to nucleate ice without microbial associates. This fits with the documented durability of sporopollenin in the spore coat (Fraser et al 2012), which has persisted in the fossil record, making it a useful tool in plant systematics (Hemsley et al 1993).…”
Section: Resultssupporting
confidence: 64%
“…Similar INA efficiencies for capsule and heated vial spores indicate that heating did not adversely impact any spore coat characteristics that might be responsible for the spore's ability to nucleate ice without microbial associates. This fits with the documented durability of sporopollenin in the spore coat (Fraser et al 2012), which has persisted in the fossil record, making it a useful tool in plant systematics (Hemsley et al 1993).…”
Section: Resultssupporting
confidence: 64%
“…Recent studies summarized by deLeeuw et al (2006) suggest that the aliphatic moieties are in fact not indigenous to the original sporopollenin and that due to burial and diagenesis the primordial biopolymer is considerably altered even in thermally immature sedimentary rocks. On the contrary,Fraser et al (2012) reported a high chemical similarity of thermally immature Pennsylvanian sporopollenin when compared to extant relatives. They concluded that land plant sporopollenin has remained stable from a chemical point of view since the Palaeozoic.Noteworthy,Watson et al (2007) pointed to another parameter that seems to influence the chemical constitution of sporopollenin.…”
mentioning
confidence: 83%
“…Although macerated, the plant and animal remains are remarkably well-preserved. The spores preserve original wall structure and sporopollenin Fraser et al 2012), and the scorpion cuticles retain much of the original chitin-protein complex (Cody et al 2011). Aromatic steroids derived from cordaites were also observed (Scott et al 2010).…”
Section: Three Upper Carboniferous (Pennsylvanian) Palaeokarst Sitesmentioning
confidence: 89%